An experimental and modelling study of a 1 kW organic Rankine cycle unit with mixture working fluid - Jung, Hyung-Chul; Taylor, L.; Krumdieck, S. (Pergamon, 2015)
The ORC (organic Rankine cycle) technology is appropriate for conversion of low-grade industrial waste heat to electrical power due to its utilization of volatile organic fluids as working fluids. It has been proposed that zeotropic fluid mixtures can improve the ORC performance compared to pure fluids. The purpose of this paper was to demonstrate the feasibility of using a zeotropic mixture as working fluid through an experimental study with a lab-scale ORC (organic Rankine cycle) test rig. In this study, a zeotropic mixture of R245fa and R365mfc (48.5%/51.5% on a mole basis) was examined by focusing on its dynamic behavior in the system until reaching steady state and the performance in a scroll expander, a finned-tube heat extractor, an evaporator and a condenser. The test rig used the exhaust gas from a 30 kW Capstone™ Gas Turbine as its heat source. Computer simulation was conducted at system level with steady state conditions and the results were compared to experimental data.